La répression des collaborations 1942-1952 : un passé toujours présent - Huyse, Luc; Dhondt, Steven; Depuydt, Paul; Hoflack, Kris; Vanhoren, Ingrid (Bruxelles : CRISP, 1993)
Bibliotheek François Vercammen
Frans
Monografie